The origins of right to work : antilabor democracy in nineteenth-century Chicago - Leon, Cedric de (ILR Press, an imprint of Cornell University Press, 2015)
"Right to Work states weaken collective bargaining rights and limit the ability of unions to effectively advocate on behalf of workers. As more and more states consider enacting right-to-work laws, observers trace the contemporary attack on organized labor to the 1980s and the Reagan era. In The Origins of Right to Work, however, Cedric de Leon contends that this antagonism began a century earlier with the Northern victory in the U.S. Civil War, when the political establishment revised the English common-law doctrine of conspiracy to equate collective bargaining with the enslavement of free white men. In doing so, de Leon connects past and present, raising critical questions that address pressing social issues. Drawing on the changing relationship between political parties and workers in nineteenth-century Chicago, de Leon concludes that if workers' collective rights are to be preserved in a global economy, workers must chart a course of political independence and overcome long-standing racial and ethnic divisions."--Publisher's website